Screening for Small Molecules' Bilayer-Modifying Potential Using a Gramicidin-Based Fluorescence Assay - Ingólfsson, Helgi I. (Mary Ann Liebert, Inc., 2010)
Many drugs and other small molecules used to modulate biological function are amphiphiles that adsorb at the bilayer/solution interface and thereby alter lipid bilayer properties. This is important because membrane proteins are energetically coupled to their host bilayer by hydrophobic interactions. Changes in bilayer properties thus alter membrane protein function, which provides a possible mechanism for “off-target” drug effects. We have previously shown that channels formed by the linear gramicidins are suitable probes for changes in lipid bilayer properties, as experienced by bilayer-spanning proteins. We now report a gramicidin-based fluorescence assay for changes in bilayer properties. The assay is based on measuring the time course of fluorescence quenching in fluorophore-loaded large unilamellar vesicles, due to entry of a gramicidin channel-permeable quencher. The method is scalable and suitable for both mechanistic studies and high-throughput screening for bilayer-perturbing, potential off-target effects, which we illustrate using capsaicin (Cap) and other compounds.